Usia Paro Hidup dan Keusangan Literatur Jurnal Skala Husada Volume 11, 12 Tahun 2014–2015 - Kartika, Putu Gede Krisna Yudhi; Ginting, Richard Togaranta; Premierita, Ni Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT This study aimed to calculate half-life and literature obsolescence of Journal Skala Husada "The Journal of Health" Volume 11 and 12, No. 1 and 2 in 2014 and 2015. The study was calculated based on the citations by each article. This study used quantitative methods, the unit analysis of this research are the articles of Journal Skala Husada "The Journal of Health" Volume 11 and 12, No. 1 and 2, in 2014 and 2015, which having citations with the year of issue. In these journals have a total 68 articles 736 citations. Based on the calculations, the highest hal-life is 8,9 years and the lowest half-life is 5,6 years, while the half-life average Journal Skala Husada "The Journal of Health" Volume 11 and 12, No. 1 and 2 of 2014 and 2015 is 6.8 years. Half-life of Journal Skala Husada "The Journal of Health" Volume 11 and 12, No. 1 and 2 in 2014 and 2015 was 6.8 years, meaning that literature which has more than 6.8 years should be reconsidered to be used as a reference while those with less than 6.8 years of age can be used as a reference for information provided is considered still relevant Keywords : half-life, obsolescence